COMPLETE AND INCOMPLETE CALCULATION: Expert Systems Apps on the Special Cases of Islamic Inheritance Law - Billah, Mu'tashim (Al-Ahwal: Jurnal Hukum Keluarga Islam, 2023)
The traditional method of resolving inheritance cases typically involves manual processes using pen and paper. However, advancements in expert systems of technology have made it possible to develop applications that expedite and simplify the calculation. This research aims to investigate the capabilities of Android-based expert systems applications in handling specific cases (masail syawadz) within Islamic inheritance law. Data were obtained by simulating cases (experiments) involving ten randomly selected inheritance apps from the Android Play Store. These applications were tested to solve al-gharawain, al-khuraqa, al-akdariyah, al-musyarakah, and al-faridah al-malikiyah cases. The research found that only two applications consistently managed to solve specific cases in Islamic inheritance law based on a particular school of thought (madhab). Other applications were only able to solve a portion of the tested cases. The majority of applications failed to identify the presented cases, although their calculations were acceptable based on one of the schools. Several factors contributed to the failure of these applications in solving inheritance cases, including limitations in simulating masail syawadz issues, inconsistency in the opinion adopted by the application developers to formulate the expert system, a limited list of available heirs, and errors in determining the portions of the heirs.[Abstrak: Kemajuan dalam sistem pakar teknologi telah memungkinkan untuk mengembangkan aplikasi yang mempercepat dan menyederhanakan perhitungan kewarisan. Penelitian ini bertujuan untuk menyelidiki kemampuan aplikasi sistem pakar berbasis Android dalam menangani kasus-kasus khusus (masail syawadz) dalam hukum kewarisan Islam. Data diperoleh dengan mensimulasikan kasus-kasus ke dalam sepuluh aplikasi warisan yang dipilih secara acak dari Android Play Store. Aplikasi-aplikasi ini diuji untuk menyelesaikan kasus-kasus al-gharawain, al-khuraqa, al-akdariyah, al-musyarakah, dan al-faridah al-malikiyah. Penelitian ini menemukan bahwa hanya dua aplikasi yang secara konsisten berhasil menyelesaikan kasus-kasus tertentu dalam hukum warisan Islam berdasarkan satu mazhab tertentu. Aplikasi lain hanya mampu menyelesaikan sebagian dari kasus-kasus yang diuji. Sebagian besarnya gagal mengidentifikasi kasus-kasus yang disajikan, meskipun perhitungan mereka diterima berdasarkan salah satu mazhab. Beberapa faktor berkontribusi pada kegagalan aplikasi-aplikasi ini dalam menyelesaikan kasus-kasus warisan, termasuk keterbatasan dalam mensimulasikan masalah-masalah masail syawadz, ketidaksesuaian dalam pendapat fikih yang diadopsi oleh pengembang aplikasi untuk merumuskan sistem pakar, daftar pewaris yang terbatas, dan kesalahan dalam menentukan bagian-bagian pewaris.]